When a Bad Bias Can Be Good: Anxiety-Linked Attentional Bias to Threat in Contexts Where Dangers Can Be Avoided - Notebaert, L.; Tilbrook, M.; Clarke, Patrick; MacLeod, C. (Sage Publications, 2017)
© 2017, © The Author(s) 2017.Anxiety vulnerability is associated with an attentional bias to threat. When threat cues signal dangers that can be mitigated through behavioural action, vigilance for these threat cues can have an adaptive function. It is unknown, however, whether the anxiety-linked attentional bias is maintained or eliminated in contexts where threat cues signal dangers that can be mitigated. The current study used a probe task to assess anxiety-linked attentional bias to threat cues signalling a danger (noise burst) that in one condition could and in another condition could not be mitigated. Results showed that high trait anxious participants exhibited a larger attentional bias to threat than low trait anxious participants, and importantly, this anxiety-linked attentional bias did not differ as a function of danger mitigability. These findings suggest that anxiety-linked attentional bias is a rather pervasive processing style that may be insensitive to contextual variation in the adaptiveness of attending to threat.